Early introduction of simulation in the medical curriculum: the MedInTo perspective - Lembo, David; Abate Daga, Federico; Calì, Corrado; Garbossa, Diego; Manfredi, Matteo; Odetto, Lorenzo; Ostacoli, Luca; Paccotti, Piero; Raimondo, Stefania; Reimondo, Giuseppe; Sciascia, Savino (Frontiers in Medicine, 2024)
Regardless the increasing body of evidence supporting the use of simulation in medicine, a question remains: when to introduce it into the medical school’s curriculum? We report the experience and future perspectives of the MD program in Medicine and Surgery of University of Turin-MedInTo. Since its launch, MedInTo has been devoted to integrating innovative teaching approaches at the early stages into the medical curriculum. Herewith, we described with a case-based approach our activities, including the use of simulation for Emergency Medical Care training for students and the integration of virtual and augmented reality technology. Dedicated surgical training activities using virtual-augmented reality and life-like simulator for students are also described.